2000
DOI: 10.1016/s0893-133x(99)00147-5
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone Alters Subjective and Psychomotor Responses to Alcohol in Heavy Drinking Subjects

Abstract: (Czirr et al. 1987;Hubbell et al. 1986;Reid et al. 1991). For example, animal studies have demonstrated slowed acquisition of alcohol self-administration (Phillips et al. 1997) and decreased alcohol consumption following administration of the non-selective opioid receptor antagonists naloxone (Froehlich et al. 1990;Hubbell et al. 1986;Hyytia and Sinclair 1993 ;Reid et al. 1991;Weiss et al. 1990), naltrexone (Altshuler et al. 1980Boyle et al. 1998;Davidson and Amit 1997 ;Myers et al. 1986;Reid et al. 1996;Volp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 36 publications
7
69
1
1
Order By: Relevance
“…These data are consistent with naltrexone metabolism previously reported in heavy drinkers and in opioid dependent subjects (McCaul et al, 2000b;Verebey et al, 1976). It has been suggested that increasing the dose of naltrexone to increase levels of naltrexone and 6-b-naltrexol in blood may be needed to achieve successful treatment in some individuals (McCaul et al, 2000a;Rohsenow, 2004). Previous studies in our laboratory have shown that doubling the dose of naltrexone from 50 to 100 mg was more effective in reducing subjective effects of alcohol (ie ratings of alcohol 'liking' and 'best effects') in heavy drinkers and also doubled the serum levels of 6-b-naltrexol (McCaul et al, 2000b).…”
Section: Discussionsupporting
confidence: 90%
“…These data are consistent with naltrexone metabolism previously reported in heavy drinkers and in opioid dependent subjects (McCaul et al, 2000b;Verebey et al, 1976). It has been suggested that increasing the dose of naltrexone to increase levels of naltrexone and 6-b-naltrexol in blood may be needed to achieve successful treatment in some individuals (McCaul et al, 2000a;Rohsenow, 2004). Previous studies in our laboratory have shown that doubling the dose of naltrexone from 50 to 100 mg was more effective in reducing subjective effects of alcohol (ie ratings of alcohol 'liking' and 'best effects') in heavy drinkers and also doubled the serum levels of 6-b-naltrexol (McCaul et al, 2000b).…”
Section: Discussionsupporting
confidence: 90%
“…that demonstrated a naltrexone-alcohol interaction in earlier analyses of combined male and female subjects (McCaul et al 2000a); current findings are based on male subjects only. Using a joystick, subjects were instructed to rate liking at the current time on a horizontal line anchored with "Not at all" on the left and "Extremely" on the right.…”
Section: Subjective Responsesmentioning
confidence: 46%
“…Psychomotor and subjective responses of male and female subjects have been reported previously (McCaul et al 2000a). …”
Section: Dependent Measuresmentioning
confidence: 95%
“…One possibility is that NTX decreases the rewarding effect of alcohol intake (Swift et al, 1994;Volpicelli et al, 1995;Sinclair, 2001). Another possibility is that NTX reduces drinking by generating aversive side effects, such as nausea, when ethanol is consumed (Davidson et al, 1999;de Wit et al, 1999;McCaul et al, 2000;Mitchell et al, 2005a). However, there is also evidence that NTX significantly reduces alcohol craving in alcoholics during abstinence (Monti et al, 1999;Rohsenow et al, 2000;O'Malley et al, 2002), and improves resistance to thoughts, urges, and behaviors associated with drinking (Anton et al, 1999).…”
Section: Introductionmentioning
confidence: 99%